Improving client-consultant-contractor communication in construction industry through whatsapp application / Muhammad Hafizul Taib - Taib, Muhammad Hafizul (2020)
A Smooth and effective communication is very important in construction industry to prevent iteration and rework which will cause money. Since there are a lot of parties involve in construction,it is important to have a good communication platform. In the current world, people are using the technology advancement to enhance the effectiveness of communication amongst people who work in construction industry. Though there are a lot of mobile application designed for construction purpose, WhatsApp is the most commonly used by all. However, there are no studies done to identify the effectiveness of it. This thesis will gather respond from client, consultant and contractor who are working in construction industry on the effectiveness of WhatsApp for the main communication platform. This thesis will also suggest on improvement to the mobile application by adding some features that the respondents think are useful to improve communication.